2018
DOI: 10.1063/1.5040114
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and selecting coarse-grain mapping operators with hierarchical graphs

Abstract: Coarse grain (CG) molecular dynamics (MD) can simulate systems inaccessible to fine grain (FG) MD simulations. A CG simulation decreases the degrees of freedom by mapping atoms from an FG representation into agglomerate CG particles. The FG to CG mapping is not unique. Research into systematic selection of these mappings is challenging due to their combinatorial growth with respect to the number of atoms in a molecule. Here we present a method of reducing the total count of mappings by imposing molecular topol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 76 publications
(66 reference statements)
2
49
0
Order By: Relevance
“…Recently, machine learning tools have facilitated the development CG force fields [9][10][11] and graph-based CG representations [12,13]. Here we propose to use machine learning to simultaneously optimize CG representations and potentials from atomistic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning tools have facilitated the development CG force fields [9][10][11] and graph-based CG representations [12,13]. Here we propose to use machine learning to simultaneously optimize CG representations and potentials from atomistic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Their theoretical model focuses on preserving most information content in the lower resolution model compared to the all atom model. Chakraborty et al 8 reported a hierarchical graph method where multiple mappings of a given molecule are encoded in a hierarchical graph, which can further be used to auto-select a particular mapping using algorithms like uniform-entropy attening. 9 In a recent systematic study on the effects of CG resolution on reproducing on and off target properties of a system, Khot et al 10 hypothesized that low-resolution CG models might be information limited, instead of having a representability limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Mapping operators used in practice for CG simulations are usually rule-based, 3,4 but recent advances have been made in algorithmic 5,8,[12][13][14][15] and unsupervised methods. 16 Rule-based schemes have xed resolution and must be created for each molecular functional group, limiting their application to sequence-dened biomolecules or polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The general practice to define a CG mapping operators has been driven by chemical intuition [63] . However, recently there have been efforts towards choosing mapping operators more systemically [64][65][66] .…”
Section: Force Matching (Learning)mentioning
confidence: 99%